DIGITAL BUSINESS LITERACY AND PRODUCT INNOVATION AS DRIVERS OF MSME SUSTAINABILITY: THE MODERATING ROLE OF DIGITAL MARKETING - Enjat Sudrajat; Verliani Dasmaran (ZILLZELL MEDIA PRIMA, 2025)
This study aims to analyze the influence of digital business literacy and product innovation on the sustainability of MSMEs in Pandeglang Regency, with digital marketing as a moderating variable. Data were obtained from 390 MSMEs through a survey using a Likert-scale questionnaire and analyzed using the Structural Equation Modeling (SEM-PLS) method. The results show that digital business literacy has a positive and significant effect on MSME sustainability, while product innovation has a negative effect without the support of an appropriate digital marketing strategy. Digital marketing does not significantly moderate the effect of digital business literacy, but weakens the effect of product innovation on MSME sustainability. These findings indicate the importance of integrating digital marketing strategies that are appropriate to the characteristics of products and digital markets to support MSME sustainability. This study provides a practical contribution to MSME development through increasing digital literacy and product innovation supported by effective digital marketing strategies.